Reconstruction of Lower Eyelid in Basal Cell Carcinoma Case with Adjunctive Hyperbaric Oxygen Therapy: A Case Report - Chietra, Yulius A. M.; Hatibie, Mendy J.; Dali, Ramli (Universitas Sam Ratulangi, 2025)
Abstract: Basal cell carcinomas (BCCs) are the most common cancers in humans, caused by exposure to ultraviolet light and are associated with PTCH1 gene mutation. Its incidence rate significantly increases per year especially in elderly people. Several modalities are available for BCC treatment but surgery is still considered as the gold standard. Oxygen is mandatory for almost all wound healing processes, and oxygen substitution can be delivered in the form of hyperbaric oxygen (HBO) therapy. We presented a 70 years old woman with a major complaint of a tumor located in the left infrapalpebral region, below the left lower lash line with 5 years of evolution. Patient had clinical presentation of solid nodular basal cell carcinoma which was the most common clinical subtype. Patient was diagnosed as having BCC based on history taking, clinical findings, and histopathological examination. Surgical wide excision, skin flap, and HBO as the adjunctive therapy were performed on this patient. With these techniques, healing time was reduced, complications rates were low, and cosmetic outcome was much better. In conclusion, closing defects of BCC case with surgical wide excision and flap yields a remarkable outcome and an adjunctive HBO therapy after surgery optimizes the oxygenation, thus, the healing potential of tissue prior to surgery, and accelerates wound healing post operatively. A good result with short healing duration was observed. Keywords: basal cell carcinoma; hyperbaric oxygen therapy; flap; wound healing